Secondary school randomized controlled interventions with a minimum dual approach to health and the links to BMI in pupils: A systematic review and meta-analysis within the project From Science 2 School - Derrick R. Tanous; Gerhard Ruedl; Mohamad Motevalli; Katharina C. Wirnitzer (Bern Open Publishing, 2024)
Introduction & Purpose Health behavior offers a pivotal domain of health for managing current global crises, including physical inactivity and overweight/obesity (Schroeder, 2007). However, adults have limited capacity for adopting healthy behavior into their lifestyle (Prochaska & Velicer, 1997). Schools offer an ideal setting for implementing health interventions considering the breadth of children that can be reached and the amount of time children spend in school (Tanous et al., 2022). The present study hypothesized that appropriately planned physical activity (PA) intervention for pupils and during compulsory secondary school time results in healthier body weight management. Methods A systematic review and meta-analysis was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guidelines, a published protocol (Tanous et al., 2022), and a trial registration was completed on the International Register of Systematic Reviews (PROSPEO: CRD4202347770). The databases searched (12/2021) included PubMed, Education Source, and EMBASE. Only school-based randomized controlled trial interventions on PA and/or diet published in English or German were included. The study population included pupils (10-19 years of age) enrolled in secondary schools and without major nutritional deficit or unstable health condition. The study sample was refined using exclusion criteria: (i) no outcome on body weight, body mass index (BMI), or self-reported, (ii) intervention groups only targeting overweight and/or obese pupils, (iii) interventions outside of regular school hours or implemented beyond the school setting, (iv) total intervention duration less than eight weeks, (v) branches of schools specializing on physical exercise/sports in general, and (vi) no control group. Title/abstract and full-text screening, data appraisal, and summary data extraction were completed by two reviewers. Results A total of 5,945 articles were identified by the search process, including 23 studies and 9,441 pupils (of which 4,787 males and 4,654 females) eligible for the analysis. PA interventions ranged from eight weeks to eight months and included jumping (n = 2), strength exercises (n = 3), cardiovascular endurance (n = 4), or a combination (n = 2). For PA intervention implemented in the secondary level school setting for at least eight weeks duration, a random effect size of -0.12 units (95% CI [-0.26. 0.02]) of BMI (kg/m2) was found with low statistical heterogeneity (I2 = 0%; p = 0.60). Discussion Due to the behavioral constraints of the school setting, children are denied from achieving the minimum level of health protection, which adversely contributes to the poor global health status with a major impact. Previous meta-analyses identified a small PA intervention effect for improving BMI in pupils (-0.02 kg/m2 and -0.05 kg/m2; Guerra et al., 2013; Harris et al., 2009) with considerable heterogeneity (I2 = 77% and 54%, respectively). The findings of the present investigation revealed a more precise effect measure than previous meta-analyses (Guerra et al., 2013; Harris et al., 2009) regarding the exclusive power of the secondary school setting over PA levels and the BMI health improvement possibility for pupils (-0.12 kg/m2). Conclusion PA intervention in secondary schools contributes to limited, yet beneficial body weight management for pupils in the ongoing global health crisis (Schroeder, 2007; Tanous et al., 2022). Considering the lack of formal organization at homes, schools are urged to achieve 60 minutes of PA daily. References Guerra, P. H., Nobre, M. R. C., Da Silveira, J. A. C., & Taddei, J. A. d. A. C. (2013). The effect of school-based physical activity interventions on body mass index: A meta-analysis of randomized trials. Clinics, 68(9), 1263-1273. https://doi.org/10.6061/clinics/2013(09)14 Harris, K. C., Kuramoto, L. K., Schulzer, M., & Retallack, J. E. (2009). Effect of school-based physical activity interventions on body mass index in children: A meta-analysis. Canadian Medical Association Journal, 180(7), 719-726. https://doi.org/10.1503/cmaj.080966 Prochaska, J. O., & Velicer, W. F. (1997). The transtheoretical model of health behavior change. American Journal of Health Promotion, 12(1), 38-48. https://doi.org/10.4278/0890-1171-12.1.38 Schroeder, S. A. (2007). Shattuck lecture. We can do better - Improving the health of the American people. The New England Journal of Medicine, 357(12), 1221-1228. https://doi.org/10.1056/NEJMsa073350 Tanous, D. R., Ruedl, G., Kirschner, W., Drenowatz, C., Craddock, J., Rosemann, T., & Wirnitzer, K. (2022). School health programs of physical education and/or diet among pupils of primary and secondary school levels I and II linked to body mass index: A systematic review protocol within the project From Science 2 School. PLoS ONE, 17(10), Article e0275012. https://doi.org/10.1371/journal.pone.0275012